SO2 sensing performance of silicon substitutional doped (8,0) carbon nanotube: A density functional theory study - Poonam Parkar; Ajay Chaudhari; Mahadev Rangnath Sonawane; Balasaheb Jijaba Nagare (Talanta Open)
This work explores the reactivity of sulfur dioxide (SO₂) when adsorbed onto silicon (Si) substitutional doped (8,0) carbon nanotube (Si-CNT) by examining the influence of Si doping on SO₂ adsorption behaviour. Silicon doping maintains the semiconducting nature of pristine carbon nanotubes, with a slight reduction in the band gap from 0.61 eV to 0.54 eV. Moreover, the minimum energy path for SO₂ adsorption on Si-CNTs reveals a chemisorptive process, with an adsorption energy of -1.66 eV, signifying an exothermic reaction where the binding energy of the product exceeds that of the reactants. Molecular orbital analysis supports these findings, showing that the lowest unoccupied molecular orbital (LUMO) is localized on the Si-CNT, while the highest occupied molecular orbital (HOMO) is predominantly located on the SO₂ molecule. Fukui function calculations further show that silicon atom plays a pivotal role by donating electrons to both, the adjacent carbon atoms and the SO₂ molecule. This electron donation leads to a notable accumulation of negative charge on the SO₂ molecule, confirming charge transfer from the Si-CNTs to SO₂. This partial ionic character in the bonding enhances the sensitivity of p-type Si-CNTs to SO₂ molecule.